A chiral cobalt(ii) complex catalyzed asymmetric formal [3+2] cycloaddition for the synthesis of 1, 2, 4-triazolines. Issue 29 (27th March 2017) - Ma, Baiwei; Luo, Weiwei; Lin, Lili; Liu, Xiaohua; Feng, Xiaoming
Abstract : A chiral N, N ′-dioxide/Co(BF4 )2 ·6H2 O complex catalysed highly efficient asymmetric [3+2] cycloaddition reaction of 5-alkoxyoxazoles with azodicarboxylate compounds. Abstract : A highly efficient catalytic asymmetric formal [3+2] cycloaddition reaction of 5-alkoxyoxazoles with azodicarboxylate compounds has been realized by a chiral N, N ′-dioxide/Co(BF4 )2 ·6H2 O complex. A series of poly-substituted 1, 2, 4-triazolines compounds were obtained in moderate to excellent yields (70–99%) with excellent enantioselectivities (82–98% ee).